2018
DOI: 10.1007/s12282-018-0884-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive immunohistochemical analyses on expression levels of hedgehog signaling molecules in breast cancers

Abstract: This comprehensive analysis demonstrated for the first time that SHH, GLI1, and GLI2 expression levels positively correlated with the malignant phenotypes of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The study revealed higher SHH immunoexpression in well-differentiated tumors than in poorly differentiated tumors, which is a similar result to the current findings for SHH mRNA expression and ccRCC grade ( 54 ). However, in breast cancer tissues, the immunoreactivity of SHH, GLI1 and GLI2 was found to be positively associated with histological grade ( 55 ), which may suggest different tendencies in the expression of SHH signaling genes depending on cancer type and histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed higher SHH immunoexpression in well-differentiated tumors than in poorly differentiated tumors, which is a similar result to the current findings for SHH mRNA expression and ccRCC grade ( 54 ). However, in breast cancer tissues, the immunoreactivity of SHH, GLI1 and GLI2 was found to be positively associated with histological grade ( 55 ), which may suggest different tendencies in the expression of SHH signaling genes depending on cancer type and histological grade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in breast cancer, Hh signaling has been shown to induce angiogenesis independently of VEGF activation [ 219 ]. Recently, a comprehensive immunohistochemistry (IHC) study by Kurebayashi et al showed that SHH expression was positively correlated with tumor size, Ki-67 labeling index, and HER2 positivity, but negatively correlated with estrogen receptor (ER+) and progesterone receptor (PR+) breast cancer [ 220 ]. In addition, a GLI1 isoform called truncated GLI1 (tGLI1) has also been reported to induce the activation of genes related to proliferation, migration, and angiogenesis of breast cancer.…”
Section: Hedgehog Signaling In Cancers and Its Inhibitorsmentioning
confidence: 99%
“…HH signaling pathway has been reported to be involved in the pathogenesis of several types of female cancer, including breast [ 20 ], ovarian [ 21 ], endometrium [ 22 ], cervical [ 23 ], and uterine leiomyosarcoma [ 24 ] ( Figure 2 ).…”
Section: Hedgehog In Female Cancersmentioning
confidence: 99%